1991
DOI: 10.1128/aem.57.1.77-84.1991
|View full text |Cite
|
Sign up to set email alerts
|

Dechlorination of Chlorocatechols by Stable Enrichment Cultures of Anaerobic Bacteria

Abstract: Metabolically stable anaerobic cultures obtained by enrichment with 5-bromovanillin, 5-chlorovanillin, catechin, and phloroglucinol were used to study dechlorination of chlorocatechols. A high degree of specificity in dechlorination was observed, and some chlorocatechols were appreciably more resistant to dechlorination than others: only 3,5-dichlorocatechol, 4,5-dichlorocatechol, 3,4,5-trichlorocatechol, and tetrachlorocatechol were dechlorinated, and not all of them were dechlorinated by the same consortium.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
23
0

Year Published

1991
1991
1999
1999

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 30 publications
(54 reference statements)
3
23
0
Order By: Relevance
“…As a consequence, their further degradation demands special attention. Chlorocatechols in anaerobic environments do not pose such fundamental problems (2). These results and the turnover experiments with DF-grown resting cells ( Fig.…”
Section: Resultssupporting
confidence: 59%
“…As a consequence, their further degradation demands special attention. Chlorocatechols in anaerobic environments do not pose such fundamental problems (2). These results and the turnover experiments with DF-grown resting cells ( Fig.…”
Section: Resultssupporting
confidence: 59%
“…For the dechlorination of PCBs, acetone, acetate, methanol, or glucose enhanced the rate [20]. Supplements of yeast extract and peptone were essential for the dechlorination of 2-chlorophenol [21], and casamino acids were supplemented in a basal medium used for the dechlorination of halo-genated aromatic aldehydes and chlorocatechols by a consortium of marine sediment bacteria [22,23].…”
Section: Resultsmentioning
confidence: 99%
“…The resorcinol product subsequently disappeared from enrichment cultures from the sludge, suggesting that anaerobic communities may be capable of mineralizing 4-chlororesorcinol. Chlorocatechols apparently result from the process of paper bleaching and other industrial processes and have recently been reported to be dehalogenated by enrichment cultures from marine sediments (5). Only certain chlorocatechol congeners were dehalogenated, and some variation in pathways was observed (Fig.…”
Section: Peak Numbermentioning
confidence: 91%
“…Subsequent studies have found similar regiospecificity for phenol dehalogenation (33,86,144). Various marine sediment enrichment cultures had distinct specificities for chlorocatechols which they dehalogenated (5). These marine sediment cultures differed in the substrates used for enrichment, which were not chlorocatechols but instead were structural analogs of chlorocatechols.…”
Section: Specificitymentioning
confidence: 95%